(untitled) (ЕтноАнтропоЗум/EthnoAnthropoZoom, 2014)
The aim of this study, on one hand, is to trace a purposeful and chronic strengthening of the Western borders as a policy of control regardless of the historical changes in the stages of development of Bulgaria. On the other hand, it’s objective is to try to open a discussion on how different performances of the border reflect on constructions of relations and perceptions of each other between representatives of the two local communities on the both sides of the state Bulgarian-Serbian border.